(3GdeUfas - (3CHh HcQ YHO Gddg Hf eMeO Hf CHj TjHI GdYHSj, GHf CHj TjHI,J (B235 (3g` s ((3GdeOQSI GdTHdjI GdMSGejI s)
(3ChdgG (B:s
(3jHJOF HaUd (B: (3ai GdQLd jbJd Ch jSJTgO , hjOaf ceG gh Ch jZSd s
(3BNQgG (B:s
(3hjfJgi HBNQ cJGH GdML s
(3Hg ChQGb eWehSI GdcJGHI HSHH EMJQGb GdMHQs
(3ef GdfSNI faSgGs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B117s
Keywords: (3GdMOjK h GdeUWdMs